Analisis Kalimat Efektif Teks Opini Bertema Sosial dalam Website “Harian Jogja” Edisi Januari 2025 sebagai Bahan Ajar Membaca Pemahaman - Silvia Eka Hariyanti; Fijri Astami Febrianti; Ida Milantika; Alexa Ayu Qurrotul Aini; Iqlima Atqiya’ul Aulia; Asep Purwo Yudi Utomo; Ferani Mulianingsih; Iwan Hardi Saputro (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study examines syntax, a branch of linguistics that investigating the structure and rules for constructing larger components such as words, phrases, clauses, and sentences. The focus of this article is on analyzing sentences found in opinion texts. The primary goal is to evaluate the effectiveness of sentences in opinion articles from the January 2025 edition of "Harian Jogja" as instructional materials for reading comprehension, particularly regarding word choice and punctuation. A qualitative descriptive method is employed, with a syntactic theoretical framework. The data presented is based on the analysis of sentence effectiveness in the opinion texts from the January 2025 edition of "Harian Jogja." Data collection includes listening and note-taking techniques, while the analysis uses the Aghigh technique. The data is informally presented in tables that highlight ineffective sentences along with their corrections. The study of three opinion texts from the "Harian Jogja" website in January 2025 resulted in a total of 147 sentences, with 118 effective and 16 ineffective sentences. Specifically, in the opinion article titled "Ethics and Productivity of Generation Z," 37 sentences were effective and 5 were ineffective; in "The Rise of Online Purchasing Fraud," 55 sentences were effective and 15 were ineffective; and in "Going through Digital Transformation: Recruitment Challenges in Banking," 26 sentences were effective and 9 were ineffective. This study aims to help distinguish between effective and ineffective sentences in texts.